Southern Ocean - Rae, Rowena (Our five oceans., 2018)
Provides a brief overview of the climate, peoples, ecosystems, and conservation of the Southern Ocean using diagrams, case studies, photographs, maps, and research activities. Includes access to audiovisual online resources, a quiz, and a glossary.